Analysis of Operating Noise Characteristics and Contribution for Automotive Seat Backrest Adjuster - Kim, Sung-Yuk; Kim, Key-Sun (International Journal of Engineering and Technology, 2018)
Background/Objectives: This study involved basic research on operating noise in an automotive seat backrest adjuster through analysis of noise sources, noise source contributions, and seat pad noise reduction effects.Methods/Statistical analysis: The test product was a driver seat of 3300cc commercial sedan. First, basic data is obtained through analysis of driving mechanism of seat backrest adjuster. Based on this, vibration and noise characteristics were analyzed by operating test of backrest adjuster, and contribution analysis to noise sources was performed. Finally, by analyzing the effect of noise reduction on the seat pad, the effect of each noise source on the backrest operating noise was determined.Findings: First, it was confirmed that the low frequency fluctuation caused by the total noise is dependent on change in the load generated by eccentric rotation of the recliner gear. Therefore, it was found that the design of the recliner gear teeth was a decisive factor in controlling the motor load. Second, the 20th order (1,320Hz) of the DC geared motor was the main cause of operating noise, which was derived from friction noise of brush-commutator and torque ripple noise. This noise accounted for more than 55% of total operating noise. In addition, the 30th order amounted to approximately 18%. In other words, the harmonic components of the DC geared motor created most of the noise, and changing the brush material and reducing torque ripple is expected to significantly improve the overall operating noise. Lastly, as a result of the seat pad noise reduction effect, total power decreased by more than 11dB (A). In addition, it was confirmed that the 20th order cause of the main noise was reduced by about 45%p.Improvements/Applications: The noise contribution of the seat recliner adjuster derived from this study can be used as a basic data for noise reduction.Â Â